DEVELOPMENT OF PROSPECTIVE AGRICULTURAL ENGINEERS’ TECHNICAL WRITING SKILLS USING ONLINE WRITING LAB - Olha Chaikovska; Iryna Humeniuk; Anastasiia Trofymenko (Novìtnâ Osvìta, 2023)
Technical writing skills allow prospective professionals to be competitive engineers, be effective at the workplace, reach high positions, and gain self-confidence in Agricultural Engineering. Therefore, technical writing is an integral part of English for Specific Purposes communication of prospective agricultural engineers. The current study aims to examine the influence of Online Writing Lab (OWL) resources on the development of students’ technical writing skills. To achieve the outlined aim, a mixed research design was employed, which involved 58 Masters of Podillia State University. Two groups were formed based on students’ preferences: experimental (n=28) and control (n=30). The Pearson criterion was used to process the results, which indicated that there was a statistically significant difference between the experimental and control groups in terms of their technical writing performances. The study has shown that using OWL resources positively influences the development of Master’s technical writing skills. OWL can be considered an effective tool for teaching students technical writing. It engages and motivates the students in technical writing skills and further self-study. Additionally, the study revealed that the majority of the students have positive attitudes toward the use of OWL resources in the learning process.